OBESITY – THE CHRONIC DISEASE OF THE 21ˢᵗ CENTURY - Vasile BOGDAN; Alexandra POP; Petre BARBOŞ (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2016)
Obesity is the scourge of humanity. Even if we aspire to a standard of living increasingly higher and more comfortable, this implies a risk to humanity, risking that through ignorance, to lead the human race from destruction. More than half the world’s population is overweight and the rate increases from year to year. The number of deaths in one year amounts to 3.4 million people. Those who remain with disabilities rises to 3.9%. Recovery costs are huge. The work aims to present how danger is the obesity and ways to prevent it. Attaining those objectives is a close collaboration between medical sciences, sport sciences, sociology, chemistry sciences. Even if exercise cannot always solve stopping and controlling obesity, it is still the least expensive of known treatments.